Role of the Vasopressin/Apelin Balance and Potential Use of Metabolically Stable Apelin Analogs in Water Metabolism Disorders - Flahault, Adrien; Couvineau, Pierre; Alvear-Perez, Rodrigo; Iturrioz, Xavier; Llorens-Cortes, Catherine (Frontiers in Endocrinology, 2017)
Apelin, a (neuro)vasoactive peptide, plays a prominent role in controlling body fluid homeostasis and cardiovascular functions. In animal models, experimental data demonstrate that intracerebroventricular injection of apelin into lactating rats inhibits the phasic electrical activity of AVP neurons, reduces plasma AVP levels, and increases aqueous diuresis. In the kidney, apelin increases diuresis by increasing the renal microcirculation and by counteracting the antidiuretic effect of AVP at the tubular level. Moreover, after water deprivation or salt loading, in humans and in rodents, AVP and apelin are conversely regulated to facilitate systemic AVP release and to avoid additional water loss from the kidney. Furthermore, apelin and vasopressin secretion are significantly altered in various water metabolism disorders including hyponatremia and polyuria-polydipsia syndrome. Since the in vivo half-life of apelin is in the minute range, metabolically stable apelin analogs were developed. The efficacy of these lead compounds for decreasing AVP release and increasing both renal blood flow and diuresis, make them promising candidates for the treatment of water retention and/or hyponatremic disorders.